PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA DAN IMBALAN FINANSIAL TERHADAP KINERJA KARYAWAN - Gelgel Atmayana, Kadek; Desi Indrawati, Ayu (E-Jurnal Manajemen, 2016)
The aim of this study was to determine the effect of transformational leadership, work discipline and financial rewards to employee performance Karma Tour and Travel Bali. This research was conducted in Karma Tour and Travel Bali with data analysis technique multiple linear regression. The number of samples obtained by using census method is as much as 89 respondents. Results of the analysis may conclude transformational leadership, work discipline and the financial rewards simultaneously positive effect on employee performance Karma Tour and Travel Bali. Transformational leadership, work discipline and financial rewards positive and significant impact on performance. This can be evidenced from the t value greater than t table. Financial rewards are the variables that most affect the performance of employees at Karma Tour and Travel Bali.
Keywords: Transformational Leadership, Work Discipline, Financial Rewards and Performance